2020
DOI: 10.1037/trm0000264
|View full text |Cite
|
Sign up to set email alerts
|

Mothers’ physical and mental health status after the homicide of their adult children in the small island state of Trinidad and Tobago.

Abstract: University of the West Indies at St. Augustine Mothers of adult children killed by homicide experience traumatic grief that is unique to this population. Yet, there is limited research on their experience and its impact on mothers' physical and mental health status. A total of 20 mothers were interviewed about their physical and mental health status after the homicide of their adult children in the small Caribbean island state of Trinidad and Tobago. This phenomenological study utilized a thematic narrative an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Indeed, psychological and psychiatric studies have confirmed the existence of an array of pathogenic effects of bereavement-such as trauma, PTSD, complicated grief, prolonged grief disorder, anxiety, depression, anger, and irritability-including for people experiencing HB, albeit with much greater severity (e.g., Burke & Neimeyer, 2014;Douglas et al, 2021;Kaltman & Bonanno, 2003;Kaplow et al, 2021;Morall et al, 2011;Powell et al, 2010;Tasker & Wright, 2020). Conducted among mixed samples of individuals experiencing HB and other forms of bereavement, with the exception of Tal et al (2017), studies substantiated and validated observations pertaining to the increased pathogenic effects of HB (Burke & Neimeyer, 2014;Douglas et al, 2021;Hinkson et al, 2020;Kaltman & Bonanno, 2003;Kaplow et al, 2021;Lenferink, van Denderen, et al, 2017;Matthews & Marwit, 2004;Miller, 2009;Morall et al, 2011;Powell et al, 2010;Rheingold & Williams, 2015;Rheingold et al, 2012;Tasker & Wright, 2020;van Denderen et al, 2016;Varga et al, 2020). Scholars conducting studies on HB's mental health' report that PTSD symptoms among individuals experiencing HB seem to be more persistent and lingering than PTSD symptoms among non-HB grieving individuals (van Wijk et al, 2017;Williams et al, 2012;Zinzow et al, 2009Zinzow et al, , 2011 and that these individuals tend to increase their use of prescribed psychotropic medication (Mezey et al, 2002) and substance abuse (Englebrecht et al, 2016;Kaplow et al, 2021).…”
mentioning
confidence: 74%
See 4 more Smart Citations
“…Indeed, psychological and psychiatric studies have confirmed the existence of an array of pathogenic effects of bereavement-such as trauma, PTSD, complicated grief, prolonged grief disorder, anxiety, depression, anger, and irritability-including for people experiencing HB, albeit with much greater severity (e.g., Burke & Neimeyer, 2014;Douglas et al, 2021;Kaltman & Bonanno, 2003;Kaplow et al, 2021;Morall et al, 2011;Powell et al, 2010;Tasker & Wright, 2020). Conducted among mixed samples of individuals experiencing HB and other forms of bereavement, with the exception of Tal et al (2017), studies substantiated and validated observations pertaining to the increased pathogenic effects of HB (Burke & Neimeyer, 2014;Douglas et al, 2021;Hinkson et al, 2020;Kaltman & Bonanno, 2003;Kaplow et al, 2021;Lenferink, van Denderen, et al, 2017;Matthews & Marwit, 2004;Miller, 2009;Morall et al, 2011;Powell et al, 2010;Rheingold & Williams, 2015;Rheingold et al, 2012;Tasker & Wright, 2020;van Denderen et al, 2016;Varga et al, 2020). Scholars conducting studies on HB's mental health' report that PTSD symptoms among individuals experiencing HB seem to be more persistent and lingering than PTSD symptoms among non-HB grieving individuals (van Wijk et al, 2017;Williams et al, 2012;Zinzow et al, 2009Zinzow et al, , 2011 and that these individuals tend to increase their use of prescribed psychotropic medication (Mezey et al, 2002) and substance abuse (Englebrecht et al, 2016;Kaplow et al, 2021).…”
mentioning
confidence: 74%
“…Belonging to a socially discriminated and marginalized ethnic or racial minority was reported to be an HB risk factor (Pavon & Basile, 2022; Stretesky et al, 2010). These studies linked racial or ethnic minority status as an HB risk factor to the recurring secondary victimization bereaved people face from society and support systems (Burke et al, 2010; Hinkson et al, 2020; Huggins et al, 2020; Laurie & Neimeyer, 2008; Sharpe, 2008; Sharpe & Boyas 2011; Sharpe et al, 2014) (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations